Challenges and Negotiations for Women in Higher Education
XX, 260 p.
Keywords: There is much ambivalence in women’s experience of the academy as teachers and students. Although today many more women follow academic careers than in the past, they do not find the welcome that they had hoped for and expected. Additionally, women students find that whilst they can now enter through the doors of universities, academic space remains embedded in structures and cultures of gender and social class. This book is a clear and accessible exploration of lifelong learning and educational opportunities for women in higher education. It has been developed from work undertaken by members of the Women in Higher Education Network with chapters organised in three thematic sections: Ambivalent Positions in the Academy Process and Pedagogy at Work Career – Identity – Home Challenges and Negotiations for Women in Higher Education is a major text in lifelong learning and educational opportunities for women in higher education. It will be a valuable resource to anyone interested in gender, research, process and practice in lifelong learning and higher education. Additionally, most women – whether or not they are part of the academy or recognise themselves as lifelong learners – will associate with many of the issues raised in this book. .